Allograft or Recipient ST2 Deficiency Oppositely Affected Cardiac Allograft Vasculopathy via Differentially Altering Immune Cells Infiltration - Zhang, Zhenggang; Zhang, Na; Shi, Junyu; Dai, Chan; Wu, Suo; Jiao, Mengya; Tang, Xuhuan; Liu, Yunfei; Li, Xiaoxiao; Xu, Yong; Tan, Zheng; Gong, Feili; et al. (Frontiers in Immunology, 2021)
The role of IL-33/ST2 signaling in cardiac allograft vasculopathy (CAV) is not fully addressed. Here, we investigated the role of IL-33/ST2 signaling in allograft or recipient in CAV respectively using MHC-mismatch murine chronic cardiac allograft rejection model. We found that recipients ST2 deficiency significantly exacerbated allograft vascular occlusion and fibrosis, accompanied by increased F4/80+ macrophages and CD3+ T cells infiltration in allografts. In contrast, allografts ST2 deficiency resulted in decreased infiltration of F4/80+ macrophages, CD3+ T cells and CD20+ B cells and thus alleviated vascular occlusion and fibrosis of allografts. These findings indicated that allografts or recipients ST2 deficiency oppositely affected cardiac allograft vasculopathy/fibrosis via differentially altering immune cells infiltration, which suggest that interrupting IL-33/ST2 signaling locally or systematically after heart transplantation leads different outcome.